2019
DOI: 10.1039/c8cc09663e
|View full text |Cite
|
Sign up to set email alerts
|

Teaching an old dog new tricks: new directions in fundamental and applied closo-carborane anion chemistry

Abstract: In this feature article we cover new directions in the fundamental and applied chemistry of the closo-carborane anions [HCB11H11]−1 and [HCB9H9]−1, including energy storage applications, ionic liquids, anionic carborane fused heterocycles/radicals, ligand substituents, and ligands for catalysis and coordination chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 89 publications
0
53
0
2
Order By: Relevance
“…In the anionic moiety,t he Zn II center is coordinated by C cage ,atrimethylamine ligand and two chlorides,which act as bridging ligands towards aL i(THF) 2 unit. Important distances are d(C1 À Zn1) = 2.032 (7) , d(Zn1 À N1) = 2.094 (8) , d(Zn1 À Cl1) = 2.327(2) ,a nd d(Zn1ÀCl1) = 2.320 (2) .S imilar to 4,t he anion 5 is monomeric and well separated from the [Li-(THF) 4 ] + cation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the anionic moiety,t he Zn II center is coordinated by C cage ,atrimethylamine ligand and two chlorides,which act as bridging ligands towards aL i(THF) 2 unit. Important distances are d(C1 À Zn1) = 2.032 (7) , d(Zn1 À N1) = 2.094 (8) , d(Zn1 À Cl1) = 2.327(2) ,a nd d(Zn1ÀCl1) = 2.320 (2) .S imilar to 4,t he anion 5 is monomeric and well separated from the [Li-(THF) 4 ] + cation.…”
Section: Resultsmentioning
confidence: 99%
“…Themonocarborane [CB 11 H 12 ] À (1)isthe monoanion that results from the formal replacement of aboron vertex in the icosahedral closo-dodecaborate [B 12 H 12 ] 2À by ac arbon atom (Figure 1a). [1,2] Polyhedral boranes and carboranes possess unique steric and electronic properties that set them apart from traditional organic or inorganic building blocks.T heir delocalized bonding and sphere-like distribution of the electron density give rise to remarkable chemical and thermal stability,i ncluding low toxicity.C arborane 1 and its halogenated and/or methylated derivatives are best known as weakly coordinating anions;related to this property,areas of application are the isolation of reactive intermediates and Lewis-acid catalysis. [3] More recently, 1 has also become ab uilding block for coordination [4] and supramolecular [5] chemistry,t he synthesis of fused 3D/2D heterocycles, [6] as well as luminescence [7] and materials science.…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the coordinating availability of 41 and 42 as WCAs using the methodd evelopedb yR eed et al and found that the coordinating availability of 41 was decreased that of [B 12 H 12 ] 2À 43,[ CB 11 H 6 Cl 6 ] À 2b,a nd wasc omparable to that of [CB 11 HCl 12 ] À 3b,o ne of the most widely used WCAs in the solid state (Table 3). [27] Even more surprisingly,d espite the fact that iodonium species are generally reactive/sensitive, the newly synthesized "clacker"-shapeda nion 42 showedh ighc hemical stability under various conditions in which the corresponding carboranyl(phenyl)iodonium 44 was convertedt oB 12 substituted C1 carborane anion derivatives 45 a-c (Scheme 14).…”
Section: Further Diversification:s Ynthesis Of Multivalent Anionic Dementioning
confidence: 99%
“…Developments of synthetic methods and functionalized molecules often go hand-in-hand. In this context, the monocarbacloso-dodecaborate(À)a nion [CB 11 H 12 ] À (1;d enoted here as "C1 carborane anion", Figure 1) has recently received increasing attention because of its unique structure andp roperties. [1] It is ar igid clusterm olecule composed of one carbon atom and eleven boron atoms, and forms ah ighly stable monochargedanion, because the negative charge is spread through-out the molecule through s-bonds.A saresult,i ts hows extremely high chemical, thermal, andp hotochemical stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation